Debating immigration in the age of terrorism, polarization, and Trump - Woods, Joshua (Lexington Books, 2017)
Debating Immigration utilizes a theoretically informed framework for analyzing the multifaceted immigration debate before and after 9/11 in the age of terrorism, political polarization, and authoritarianism.